Dyscalculia among first circle student’s primary schools in primary schools - Mrywan Abdulmajeed; Ali, Suzan Mahmuod; Hoshiar, Payam; Sardar , Gashbin (Journal of University of Human Development, 2024)
The aim of this research was to investigate dyscalculia among first circle students in primary schools in terms of gender, class, and school. Dyscalculia is a specific learning disorder that effects a student’s ability to learn math. This study included first grade students in first, second and third grades in chamchamacl city- Suliamnai governorate. The most important theories presented in this study which were interest cognitive construction theory, Piaget's theory of cognitive development, Triple Code Model of imagery and the model of number processing system, these help us to better understand dyscalculia. In addition, previous studies suggest that some environmental, social, psychological, educational and genetic factors cause this phenomenon. The researchers used a preliminary survey and translated it into Kurdish, which consists of 22 items. After receiving the opinion of experts, 102 students were taken from the perspective of teachers. Data were analyzed using statistical process (SPSS-26)., and also this study has very good validity and stability. In addition, the results showed that the rate of dyscalculia among girls were higher than boys and it was more prevalent in public schools, especially among second grade students. This study highlighted several limitations and recommendations, for instance, it was conducted only a small number of teachers, therefore, it suggested to involve other group of students., and also it is highly is suggested to use more assessments, tools, and interviews to diagnose the symptoms dyscalculia.